Kebiasaan Makan Sayur Blendrang berhubungan dengan Tekanan Darah Pasien Hipertensi - Deka Ade Yussmawan; Abu Bakar; Erna Dwi Wahyuni (Critical Medical and Surgical Nursing Journal (CMSNJ), 2019)
Introduction: Hypertension is a real condition with increased blood pressure in the arteries. Puskesmas Ngrambe is one of Puskesmas with highest case of hypertension at Ngawi. Hypertension is largely due to modern lifestyle , excess weight and diet, included blendrang habits consumptions. This study was aimed to investigate correlating blendrang habits consumption with hypertension incidence on hypertension patients at Puskesmas Ngrambe.Method: This study used a cross-sectional design. The indepedent variable is blendrang consumptions, and the dependent variabel is hypertension incidence.  Total sampel was 34 respondents, taken according inclusion criteria by purposive sampling. Data were analyzed using Spearman's Rho test with a significance level of α = 0.05.Result: The results showed that p=0.004. It can be concluded that blendrang habits consumption was a significant corelations with hipertension incidence on Hypertension patients at Puskesmas Ngrambe.Discussion: Recommended for health practisioner to provide health promotion knowledge about hypertension and nutrition to reduce cases of hypertension. Further research expected to analysis other factors related to hypertension incidence at Puskesmas Ngrambe.